Concentration of the combined drag with antimicrobic and antiinflammatory action in rabbits eye anterior chamber at local introduction - I. N. Okolov; C. A. Nikulin; T. K. Churakov; T. E. Morozova; N. V. Krivorotova; G. V. Karakashev; E. I. Savel’eva (Oftalʹmologiâ)
Aim was to research objective consisted in an assessment of penetration of an antibacterial preparation of ciprofloxacin and a corticosteroid preparation of dexamethasone as a part of Kombinil-Duo’s combined medicinal form in moisture of the forward camera of an eye in experiment, and also in detection of the minimum overwhelmingconcentration (MOC) of ciprofloxacin in VPKG for the most frequent causative agents of eye infections.Material and methods. In experiment on seven adult individuals of rabbits of breed the Chinchilla (fourteen eyes) eye drops Kombinil — Duo, containing in quality of the main substance ciprofloxacin (3 mg / ml) and dexamethasone(1 mg / ml) are tested. Determination of concentration of the main substances of studied preparations in moisture of the eye camera carried out a method of a highly effective liquid chromatography (VEZhH) in combination with mass and spectrometer detecting (MS) on the liquid Shimadzu LC-20AB chromatograph with the mass and selectivedetector Shimadzu LCMS-2010EV (ESI).Results and conclusion. The maximum concentration of ciprofloxacin in moisture of the forward camera of rabbits eye made 0,25 mkg / ml, and minimum — 0,06 mkg / ml, average concentration — 0,13±0,06 mkg / ml. The anti-inflammatory component presented by dexamethasone in a studied eye form, is defined in the range from 0,14 to 0,63 mkg / ml. Average concentration of dexamethasone equaled 0,24±0,12 mkg / ml. The obtained data testify that average concentration of ciprofloxacin in VPKG exceeds average MPK90 for strains the grampolozhitelnykhof bacteria which are potential activators of postoperative infectious complications: metitsillinchuvstvitelny golden стафилококки (MPK90‑0,06 mkg / ml) and ftorkhinolonchuvstvitelny koagulazonegativny стафилококки (mkg / ml MPK90–0,05). The revealed concentration are sufficient for minimization of risk of development of postoperativeinfectious complications. In a pilot study it is shown that at an instillation in a conjunctival bag of rabbits of a complex preparation of Kombinil-Duo in moisture of the forward camera of an eye concentration of antibacterial means (ciprofloxacin) sufficient for suppression of the main activators causing postoperative complications with ensuring antiinflammatory action (at the expense of dexamethasone) is created. The obtained data can be used in clinical practice for correction of schemes on treatment and prevention of inflammatory diseases of eyes.